Interview with Ian Burns, artist, New York, 3 October 2012 - Messham-Muir, Kit (StudioCrasher, 2015)
Ian Burns is an Australian-American artist, who went from Newcastle in Australia to New York to study, and ended up staying. He now has a significant international art practice. Much of his work has a particular humour to it as well as a more serious social and political dimension. I met with Ian in his studio in Long Island City, New York, where we discussed his practice and the impact of media and technology on contemporary visual culture.